2021
DOI: 10.1186/s12888-021-03130-4
|View full text |Cite
|
Sign up to set email alerts
|

The associations between maternal and child diet quality and child ADHD – findings from a large Norwegian pregnancy cohort study

Abstract: Background Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder. Effective long-term treatment options are limited, which warrants increased focus on potential modifiable risk factors. The aim of this study was to investigate associations between maternal diet quality during pregnancy and child diet quality and child ADHD symptoms and ADHD diagnosis. Methods This study is based on the Norwegian Mother, Father a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…We found no evident associations between other not-carbonated sweet drinks and offspring ADHD, and our results might reflect that women who consume carbonated sweet drinks report ADHD symptoms differently than women who do not consume carbonated drinks. Our findings are also compatible with a recent study from the MoBa cohort that found higher overall maternal diet quality to be associated with slightly lower ADHD symptom scores and risk of ADHD diagnoses in offspring aged 8 years [ 13 ]. The maternal diet quality was assessed using a composite index where added sugar was one of the components.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no evident associations between other not-carbonated sweet drinks and offspring ADHD, and our results might reflect that women who consume carbonated sweet drinks report ADHD symptoms differently than women who do not consume carbonated drinks. Our findings are also compatible with a recent study from the MoBa cohort that found higher overall maternal diet quality to be associated with slightly lower ADHD symptom scores and risk of ADHD diagnoses in offspring aged 8 years [ 13 ]. The maternal diet quality was assessed using a composite index where added sugar was one of the components.…”
Section: Discussionsupporting
confidence: 92%
“…So far, such possibilities have been less studied in relation to ADHD. A recent study from the Norwegian Mother and Child Cohort Study, however, found that overall maternal diet quality and lower intake of ultra-processed foods were weakly associated with the child’s ADHD symptoms at 8 years of age [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Association was found between ADHD, and the mother’s altered nutritional and metabolic status [ 8 ]. In contrast, a healthy diet without ultraprocessed products [ 9 ] and a diet with a low inflammatory index (DII) during pregnancy [ 10 ] are associated with a lower incidence of ADHD in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in MoBa have shown that maternal diet quality described by various measures of a healthy diet, is associated with a decrease in ADHD symptoms and diagnosis at 8 years [ 39 ], and that higher maternal intake of unhealthy foods during pregnancy predict emotional problems among children at the age of five [ 40 ]. However, our study is, to our knowledge, one of few that has explored associations between both maternal and child dietary patterns and child communication and motor development at multiple timepoints.…”
Section: Discussionmentioning
confidence: 99%